1992
DOI: 10.1128/iai.60.10.3962-3970.1992
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human T-cell epitopes on the S4 subunit of pertussis toxin

Abstract: Ten adult humans were vaccinated with the Japanese acellular pertussis vaccine JNIH-3, containing detoxified pertussis toxin (PT), formaldehyde, and filamentous hemagglutinin. The vaccination induced a specific antibody response to PT and filamentous hemagglutinin, and a Western blot (immunoblot) analysis of the antibody response to PT revealed antibodies to PT subunits Si, S2, S3, S4, and S5. The response of peripheral lymphocytes to PT was assessed in an in vitro proliferation assay. A proliferative response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…It was found that the peptides corresponding to the T-cell epitopes identified following immunization with the B oligomer were able to induce in vitro proliferative responses to PT components containing subunit S4. One of the murine T-cell epitopes identified in the present study corresponded to one of the major human T-cell epitopes identified in an earlier study (35). These results raise the possibility of using mice as a model for development of a synthetic immunogen based on defined T-and B-cell epitopes from PT.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…It was found that the peptides corresponding to the T-cell epitopes identified following immunization with the B oligomer were able to induce in vitro proliferative responses to PT components containing subunit S4. One of the murine T-cell epitopes identified in the present study corresponded to one of the major human T-cell epitopes identified in an earlier study (35). These results raise the possibility of using mice as a model for development of a synthetic immunogen based on defined T-and B-cell epitopes from PT.…”
supporting
confidence: 81%
“…No proliferative responses to the 12-residue peptides were found. In a previous study, PT-immune human peripheral lymphocytes were likewise stimulated in vitro with the 12-residue peptides, and no proliferative responses were found (35). The lack of responses to the 12-residue peptides is probably due to the fact that 12 amino acids in some cases may be too few to make up a T-cell epitope (19).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations